2019
DOI: 10.1111/jnc.14891
|View full text |Cite
|
Sign up to set email alerts
|

A multimolecular signaling complex including PrPC and LRP1 is strictly dependent on lipid rafts and is essential for the function of tissue plasminogen activator

Abstract: Prion protein (PrPC) localizes stably in lipid rafts microdomains and is able to recruit downstream signal transduction pathways by the interaction with promiscuous partners. Other proteins have the ability to occasionally be recruited to these specialized membrane areas, within multimolecular complexes. Among these, we highlight the presence of the low‐density lipoprotein receptor‐related protein 1 (LRP1), which was found localized transiently in lipid rafts, suggesting a different function of this receptor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 67 publications
3
35
1
Order By: Relevance
“…Since its discovery, various authors have showed that PrP C is present on the cell plasma membrane-associated with different gangliosides and cholesterol-within particular structures named "lipid raft microdomains" [21,47]. These structures represent domains of plasma membrane that contain high concentrations of cholesterol and glycosphingolipids, such as GM3, GM1, GD3, and proteins; lipid rafts can dissociate and associate rapidly, forming functional clusters in cell membranes [22,48].…”
Section: Prion Protein As Raft Componentmentioning
confidence: 99%
See 2 more Smart Citations
“…Since its discovery, various authors have showed that PrP C is present on the cell plasma membrane-associated with different gangliosides and cholesterol-within particular structures named "lipid raft microdomains" [21,47]. These structures represent domains of plasma membrane that contain high concentrations of cholesterol and glycosphingolipids, such as GM3, GM1, GD3, and proteins; lipid rafts can dissociate and associate rapidly, forming functional clusters in cell membranes [22,48].…”
Section: Prion Protein As Raft Componentmentioning
confidence: 99%
“…These clusters, present in the outer monolayer of the plasma membrane, provide highly efficient lipid-protein modules, which operate in membrane trafficking and cell signaling [52]. Several authors theorized lipid rafts as sequestering platforms of specific proteins, thus modulating cell signaling [21,53,54].…”
Section: Prion Protein As Raft Componentmentioning
confidence: 99%
See 1 more Smart Citation
“…[78,79] The role of lipid rafts in the recruitment and activation of downstream signal transduction pathways, such as those mediated by the interaction of PrP c , has been studied in human neuroblastoma cell lines. [80] Alteration of the lipidic content of lipid rafts perturbs the physical/functional interaction between PrP c and other proteins, thus inhibiting downstream responses. [80] However, apart from physiological roles of PrP c , it is long known that altered, protease-resistant, prion protein (PrP sc ) is involved in the pathogenesis of neurodegenerative prion diseases.…”
Section: Sqsis and Alzheimer's/prion Diseasementioning
confidence: 99%
“…[80] Alteration of the lipidic content of lipid rafts perturbs the physical/functional interaction between PrP c and other proteins, thus inhibiting downstream responses. [80] However, apart from physiological roles of PrP c , it is long known that altered, protease-resistant, prion protein (PrP sc ) is involved in the pathogenesis of neurodegenerative prion diseases.…”
Section: Sqsis and Alzheimer's/prion Diseasementioning
confidence: 99%